2011
DOI: 10.1038/tp.2011.24
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic regulation of Nrnx1 expression: an integrative cross-species analysis of schizophrenia candidate genes

Abstract: Neurexin 1 (NRXN1) is a large presynaptic transmembrane protein that has complex and variable patterns of expression in the brain. Sequence variants in NRXN1 are associated with differences in cognition, and with schizophrenia and autism. The murine Nrxn1 gene is also highly polymorphic and is associated with significant variation in expression that is under strong genetic control. Here, we use co-expression analysis, high coverage genomic sequence, and expression quantitative trait locus (eQTL) mapping to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 92 publications
0
24
0
Order By: Relevance
“…GSK3B is a proline-directed serine–threonine kinase and involved in neuronal cell development (55). This gene had been reported to play important roles in many neurology diseases, such as Parkinson’s disease (56), bipolar disorder (57) and schizophrenia (58). NFAT5 belongs to the protein family of the nuclear factors of activated T cells (NFAT) and plays a key role in inducible gene transcription during the process of immune response.…”
Section: Resultsmentioning
confidence: 99%
“…GSK3B is a proline-directed serine–threonine kinase and involved in neuronal cell development (55). This gene had been reported to play important roles in many neurology diseases, such as Parkinson’s disease (56), bipolar disorder (57) and schizophrenia (58). NFAT5 belongs to the protein family of the nuclear factors of activated T cells (NFAT) and plays a key role in inducible gene transcription during the process of immune response.…”
Section: Resultsmentioning
confidence: 99%
“…WGCNA was used to show that it was at the level of network structure and not differential expression that one could discriminate the nonhuman primate and human brain transcriptome and the regional brain differences in the human transcriptome [40], [41]. Importantly from a translational prospective, recent work has demonstrated that eQTL in combination with coexpression network analysis can identify novel candidate genes related to schizophrenia [42], [43]. The WGCNA has been used to dissect the transcriptome into modules associated with specific cell types (neurons, oligodendrocytes, astrocytes and microglia), specific organelles and synaptic functions [41]; our data replicated this observation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, significant numbers of dentate gyrus granule cells were histologically and electrophysiologically immature, more than would be predicted based on proliferation rates and the tempo of normal development, and these mice showed severe impairments in working memory . Neurexins (NRXNs) and neuroligins (NLGNs) are families of synaptic proteins, which are known to be risk factors for schizophrenia (Novak et al 2009;Rujescu et al 2009;Ikeda et al 2010;Gauthier et al 2011;Mozhui et al 2011;Sun et al 2011;Yue et al 2011). These proteins are synaptic cell-adhesion molecules involved in various neuronal processes, including differentiation, maturation, stabilization, and plasticity of both inhibitory and excitatory synapses (Bang and Owczarek 2013).…”
Section: Adult Neurogenesis and Psychiatric Disordersmentioning
confidence: 99%